Strategic Science Translation and Environmental Controversies. (November 2015) - Cordner, Alissa
In contested areas of environmental research and policy, all stakeholders are likely to claim that their position is scientifically grounded but disagree about the relevant scientific conclusions or the weight of the evidence. In this article, I draw on a year of participant observation and over 110 in-depth interviews, with the case study of controversial chemicals used as flame retardants in consumer products. I develop the concept of strategic science translation (SST), the process of interpreting and communicating scientific evidence to an intended audience in order to advance certain goals and interests. Engaging in selective, interpretive, or inaccurate SST allows competing stakeholders to bolster their arguments, strengthen their authority, and inspire change regarding a policy-relevant issue. Because stakeholders deploy imbalanced resources when they participate in contested environmental fields, their actions in those fields and the resulting policy outcomes often reduce not to the settling of scientific truths but to power differentials.